Aristotle's Theory of definition (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Through this research we try to concentrate on an essential and important issue in ancient logic which is the theory of definition related  to Aristotle . where we are going to discuss the definition related to Aristotle in details, and try to clarify his point of view if his definition  eral or nominal. and if the definition in his point of view for species or individuals and this means if it refers total perception or partial individual and if it refers to the quiddity of a thing or to show it's properties.And we will try to show his opinion of predicable and if they have an existence outside or they are only names haven't any existence outside minds.